Key Success Factors for Digital Transformation in Indonesia’s International Freight Forwarding: Analyzing Barriers for Traditional Freight Forwarders - Patricia Joanne (Green Publisher Indonesia, 2025)
Indonesia's strategic geographic position makes it a key player in global trade, yet its logistics sector faces significant challenges due to low digital transformation levels. This study aims to identify key success factors to address barriers faced by traditional freight forwarders and accelerate digital adoption. A comprehensive methodology was employed, including a literature review, surveys and questionnaires with 102 industry participants, and case studies of successful digital freight forwarders globally. The findings highlight 13 critical KSFs encompassing leadership commitment, strategic planning, workforce empowerment, technological integration, financial incentives, and collaborative efforts. These factors collectively provide a roadmap for overcoming the barriers to digital transformation and enhancing competitiveness in Indonesia's logistics sector. Furthermore, this research opens multiple avenues for future exploration, such as examining leadership styles, understanding customer perceptions, and analyzing the socio-cultural impacts of digitalization on logistics operations.